Carbon Anode for the Formation of Carbon Monoxide and its Impact on the Molten-salt Electrolysis - Li, Ze-quan; Guo, Jing; Hu, Rong; Ru, Li-yue; Wang, Hai-hua (Asian Journal of Chemistry, 2014)
Based on the theoretical calculation and experimental investigation, the formation of carbon monoxide in off-gas and its impact on molten-salt electrolysis of TiO2 were first studied. Flue gas analyzer was used to detect CO content in off-gas of the molten-salt electrolysis. X-ray diffraction was used to determine the phase composition of the products of electrolysis. It indicated that the CO is formed by the two ways. A part of CO is formed by the reaction between carbon and oxygen gas, which is the main anodic reaction. The other part of CO is generated by the side reactions. The results showed that the CO and CO2 cannot vent timely so as to cause the side reactions, such that influence the efficiency of electrolysis and the purity of cathode products.